Peran Business Model Inovation pada Industri Kuliner Cake Shop Berbasis Syariah - Putri Nur Alfisyahri; Nurbaiti Nurbaiti; Muhammad Ikhsan Harahap (UNIVED Press, 2023)
This study aims to determine the role of Business Model Innovation in the Sharia-based Cake Shop Culinary Industry. This Business Model Innovation itself focuses on innovation in the internal environment such as management, human resources who manage, and internal companies, besides internal, Business Model Innovation also innovates companies such as utilizing developing technology. This research method is the research approach used is a descriptive qualitative approach. The subjects in this study were conducting in-depth interviews with the head of the IMA BROWNIES cake and bakery shop and the employees who work at the bakery. The results of the study are that the overall level of product innovation at the IMA BROWNIES cake and bakery shop is in a good category. This shows that the innovation made by the IMA BROWNIES cake and bakery shop is evidenced by the increase in sales volume every month. IMA BROWNIES cake and bakery shop applies the six bases of product innovation as follows: Modulation-based innovation is done by increasing product characteristics Size-based innovation is done by changing the size of bread ranging from small to large sizes. Design-based innovation is done by changing the appearance of the bread shape with a unique and attractive shape. For technological innovation, IMA Brownies store itself has not used fintech, for payments and orders they are still manual and only sell in stores. Business Model Innovation carried out by IMA BROWNIES cake and bakery is proven to be able to increase sales of IMA BROWNIES cake and bakery by seeing an increase in buyers. IMA BROWNIES cake and bakery can increase sales by innovating products, increasing sales is the goal of innovation carried out by IMA BROWNIES cake and bakery so as to increase sales.